Quality of Life in Patients with Melasma - Reza Almasi Ghale; Maryam Nasimi; Saeideh Alidoost; Marjan Talebi; Rouzbeh Almasi Ghale; Mehregan Rahmani; Farkhondeh Pouresmaeili (Dermatology Practical & Conceptual)
Introduction: Melasma is a skin disorder that causes brown spots on the face, especially in women and people with dark skin. This situation can have a significant impact on the patient's quality of life, including issues with self-confidence, mental strain, and difficulty in social and familial relationships.